Synthesis and Characterization of a Linear [Mn3(O2CMe)4(py)8]2+ Complex - Eleni E. Moushi; Christos Kizas; Vassilios Nastopoulos; Anastasios J. Tasiopoulos (Bioinorganic Chemistry and Applications)
Two new compounds that consist of the linear trinuclear manganese(II) cation [Mn3(O2CMe)4(py)8]2+ cocrystallizing with different counteranions (I3-, [1]; ClO4-, [2]) are reported. Complex 1 was prepared from the reaction of [Mn(O2CMe)2]⋅4H2O with I2 in MeCO2H/py, whereas complex 2 was isolated from the reaction of [Mn3O(O2CMe)6(py)3]⋅py with [Mn(ClO4)2]⋅6H2O in MeCN/py. The crystal structures of both compounds were determined by single crystal X-ray crystallography. Magnetic susceptibility studies that were performed in microcrystalline powder of 1 in the 2–300 K range revealed the presence of antiferromagnetic exchange interactions that resulted in an S=5/2 ground spin state.